Administration of Bifidobacterium breve PS12929 and Lactobacillus salivarius PS12934, Two Strains Isolated from Human Milk, to Very Low and Extremely Low Birth Weight Preterm Infants: A Pilot Study. (22nd February 2015) - Moles, Laura; Escribano, Esperanza; de Andrés, Javier; Montes, María Teresa; Rodríguez, Juan M.; Jiménez, Esther; Sáenz de Pipaón, Miguel; Espinosa-Martos, Irene
Abstract : The preterm infant gut has been described as immature and colonized by an aberrant microbiota. Therefore, the use of probiotics is an attractive practice in hospitals to try to reduce morbidity and mortality in this population. The objective of this pilot study was to elucidate if administration of two probiotic strains isolated from human milk to preterm infants led to their presence in feces. In addition, the evolution of a wide spectrum of immunological compounds, including the inflammatory biomarker calprotectin, in both blood and fecal samples was also assessed. For this purpose, five preterm infants received two daily doses (~10 9  CFU) of a 1 : 1 mixture of Bifidobacterium breve PS12929 and Lactobacillus salivarius PS12934. Bacterial growth was detected by culture-dependent techniques in all the fecal samples. The phylum Firmicutes dominated in nearly all fecal samples while L. salivarius PS12934 was detected in all the infants at numerous sample collection points and B. breve PS12929 appeared in five fecal samples. Finally, a noticeable decrease in the fecal calprotectin levels was observed along time.